FUNGSI NOTARIS SELAKU PEJABAT PEMBUAT AKTA IKRAR WAKAF (PPAIW) DALAM PERUBAHAN PERUNTUKAN HAK ATAS TANAH WAKAF - Utami, Muhammad Khoirul (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2017)
The thesis entitled "The role of the Notary Deed Official Pledge As Waqf In the allotment of Land Rights Amendment Waqf" examines the waqf land already diwakafkan by wakif and run through the process of making the Pledge of Endowments and already certified waqf land. However, the waqf land area experiencing growth and progress resulting in a change General Spatial Plan (which disturb the position of the donated land. Based on the above, the writers compose thesis raises the issue of whether the allotment of land endowments can be changed, how the role of the notary as Officer Deed of Pledge Waqf in the change designation of land rights endowments, and any obstacles in the change designation of land rights waqf , In writing this thesis, the author uses the normative method. It can be concluded that the change of land designation endowments can be done on the condition that these changes to the public interest in accordance with the General Spatial Plan which is based on the law and not contrary to Islamic principles, changes in the allotment of land endowments can be done after approval Ministry of Religious Affairs on consideration of Indonesian waqf Board and the replacement of at least one rank and balanced with original waqf property. The role of the Notary as Officer Deed of Pledge Waqf  is to legalize or register the minutes of the meeting of the board of supervisors, made a deed of exchange of land endowments, making back Deed of Pledge Waqf of land which has been exchanged in accordance with the Deed of Pledge Waqf originally , providing information on the legal acts penghadap. Barriers to change the designation of land rights endowments of which is still going controversy about peraliahan rights to the donated land, the lack of public understanding of the donated land so many waqf land that is not registered and does not have a certificate endowments, as well as a lack of public understanding of the transfer of rights over donated land, if there is a legal act on changes in land endowments frequent rejection, and understanding Nazhir towards waqf property itself is still lacking, as well as other obstacles.